2016
DOI: 10.1038/ijir.2016.21
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory evoked potentials assess the efficacy of circumcision for premature ejaculation

Abstract: To assess the efficacy and mechanism of circumcision in the treatment of premature ejaculation (PE) with redundant prepuce, we enrolled a total of 81 PE patients who received circumcision. The patients' ejaculatory ability and sexual performances were evaluated before and after circumcision by using questionnaires (Intravaginal ejaculation latency time (IELT), Chinese Index of PE with 5 questions (CIPE-5) and International Index of Erectile function- 5 (IIEF-5)). Furthermore, somatosensory evoked potentials (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…severity of erectile dysfunction (ED) based on the IIEF-5 score (severe 1-7; moderate 8-11; mild to moderate 12-16; mild 17-21; no erectile dysfunction [22][23][24][25]. As per this scale, before circumcision, a particular number of patients belonged to the mentioned groups: 23 (33.3%) severe; 4 (5.8%) moderate; 8 (11.6%) mild to moderate; 14 (20.3%) mild; 20 (29.0%) no ED.…”
Section: Resultsmentioning
confidence: 99%
“…severity of erectile dysfunction (ED) based on the IIEF-5 score (severe 1-7; moderate 8-11; mild to moderate 12-16; mild 17-21; no erectile dysfunction [22][23][24][25]. As per this scale, before circumcision, a particular number of patients belonged to the mentioned groups: 23 (33.3%) severe; 4 (5.8%) moderate; 8 (11.6%) mild to moderate; 14 (20.3%) mild; 20 (29.0%) no ED.…”
Section: Resultsmentioning
confidence: 99%
“…Level of evidence Grade Secondary data from RCTs 1þþ A Kigozi et al 20,08 7 Krieger et al 20,08 8 Systematic reviews 1þ A Morris & Krieger 2013 15 Tian et al 2013 18 Shabanzadeh et al 20 Yang et al 2018 19 Meta-analyses 1þ A Tian et al 2013 18 Yang et al 2018 19 Longitudinal cohort studies 2þþ B Nordstrom et al 2017 27 Galukande et al2017 28 Retrospective cohort studies 2þþ B Laumann et al 1997 30 Mao et al 2008 21 Ferris et al 2010 31 Hoschke et al 2014 33 Homfray et al 2015 35 Chinkoyo & Pather 2015 36 Jönsson et al 2015 37 Collins et al 2002 38 Fink et al 2002 41 Senkul et al 2004 42 Physiological measurements 2þþ B Waldinger et al 2005 51 Waldinger et al 2009 53 Alp et al 2014 55 Xia et al 2016 58 Penile sensitivity Physiological measurements 2þþ B Bleustein et al 2005 59 Payne et al 2007 60 Bossio et al 2016 64 Secondary data from RCT 1þþ A Krieger et al 2008 8 Systematic Reviews 1þ A Cox et al 2015 12 Morris & Krieger 2013 15 Shabadnazeh et al 20…”
Section: Type Of Study and Referencesmentioning
confidence: 99%
“…56,57 In 2016, Xia et al measured somatosensory evoked potentials (SEP) of 81 men who were circumcised to treat redundant prepuce or PE. 58 The latency of the glans penis SEP was prolonged after 59 Measurement assessed vibration, pressure, and spatial perception, together with thermal thresholds for warmth and cold. Uncircumcised men were tested with and without their foreskin retracted.…”
Section: Physiological Measurementsmentioning
confidence: 99%
“…In a study, Gallo performed distal circumcision to men with lifelong PE and reported that distal circumcision is an effective treatment for PE (Gallo, 2017). Xia et al investigated men circumcised in adult life, who had somatosensorial evoked potentials, and did not find a therapeutic or pathological effect of circumcision on PE (Xia et al., 2016). However, the psychological effect of circumcision, especially on children is a neglected field with only a handful of studies having been published.…”
Section: Discussionmentioning
confidence: 99%